Spotkanie z wybranymi tekstami kultury popularnej. W stronę relacyjnego bycia w świecie - Adamska-Staroń , Monika (Studia Edukacyjne, 2020)
This text aims to familiarize the reader with a certain way of thinking about the category of meeting, selected pedagogical consequences that can take place as a result of young people’s encounter with texts of popular culture, especially with rock music and film, and to include the recipient in the discussion of the presented issue. The text consists of three parts. The first part is an introduction to the range of questions and treats the meeting as a pedagogical category. The second section focuses on the phenomenon of meeting texts of popular culture, more specifically rock and film narratives, while the third, summarizing part describes the meeting of young people with rock narratives on the basis of the results of the author’s own research.